(untitled) (Ahkam: Jurnal Hukum Islam, 2014)
Punishment is a severe physical action by person(s) from high stratum to the person(s) of lower stratum which is commonly intended to show off the power. In the context of education, punishment is done to students to make them realize their mistake and so, they do not make the same mistake in future. However, according to the teaching of Islam, punishment must not be conducted to children unless they make mistake and it is conducted evenly so that it does not remain on physical suffer. Punishment may only be done to make children learn Islam better. Kata kunci: Hukuman, Pendidikan Anak, Hukum Islam